An Energy-efficient Data Transmission Scheme in Underwater Wireless Sensor Networks - Emami, Y.; Javidan, R. (Engineering, Technology & Applied Science Research, 2016)
Energy is a precious resource in underwater wireless sensor networks (UWSNs). In these networks, the number of data transmissions between sensor nodes dominates energy consumption. Complex signal processing techniques also increase energy consumption. In this paper an energy-efficient data transmission scheme based on bloom filters is proposed. Extensive simulation is carried out to demonstrate the effectiveness of the proposed method. Simulation results indicate that the proposed scheme outperforms the primary technique in terms of energy efficiency, lifetime, load and loss rate. The results of this research suggest that exploiting bloom filters is a viable solution for reducing the number of transmissions in UWSNs.